Pioneer of climate-neutral energy generation – Brazil - Kress, Hannelore [Verfasser]; Giebeler Santos,Julia [Verfasser] (My University, 2024)
„Germany and Brazil have been collaborating on sustainability issues for a long time. Germany supports Brazil in sustainable energy and protecting tropical forests. The potential of biomass, sun, and wind will be better utilised. The vocational training system in Brazil needs improvement to meet the demands of the green transition. Julia Giebeler Santos manages a project that advises the Ministry of Education and other relevant organisations to develop green sector education and training. The Ministry of Education has already integrated sustainability into vocational training, with a focus on renewable energy. The public vocational schools have been equipped with solar panels and teachers have been trained for curriculum development. However, vocational education still faces challenges such as drop-out rates and negative reputation of vocational education in general.“ (authors‘ abstract; BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 2.3.3 Lateinamerika; 370; Berufsbildung; Nachhaltige Entwicklung; Internationale Zusammenarbeit; Systemberatung [Berufsbildung]; Bundesrepublik Deutschland; Brasilien